The interactive effect of grazing and fertilizer application on soil properties and bacterial community structures in a typical grassland in the central Inner Mongolia Plateau - Qi, Le; Zhang, Min; Yin, Jingjing; Ren, Weibo; Sun, Siyuan; Chen, Zhe; Yuan, Ting; Guo, Luyao (Frontiers in Ecology and Evolution, 2023)
Appropriate grazing pressure and fertilizer application of nitrogen (N) and phosphorus (P) are effective measures to increase grassland productivity. In this study, we report on the interactive effects of grazing intensity and fertilizer application on soil properties, enzyme characteristics, and soil bacterial community compositions. The experiment was set up in a typical grassland in Xilingol, Inner Mongolia, and had 12 treatments (CC, CN, CP, CNP, LC, LN, LP, LNP, HC, HN, HP, and HNP). These consisted of three grazing intensity levels crossed with four fertilizer application treatments: no fertilizer, N fertilizer, P fertilizer addition alone, and both N and P fertilizers addition, subjected to field sampling and laboratory analysis. The results showed that soil alkaline hydrolysis nitrogen was increased by 15 and 13.6% in LN over LC in the 0–10 and 10–20 cm soil depth layers, respectively. Soil available P was 135.6% higher in LP than in LC at 0–10 cm but similar between LP and LC at 10–20 cm. Soil urease activity rose by 46.8 and 39.3% in 0–10 cm soil and was augmented by 63.1 and 60.3% in 10–20 cm soil of LN and LP relative to LC, respectively. Soil catalase (CAT) activity was decreased in response to LNP by 29.4, 23.5, and 26.5% vis-à-vis LC, LN, and LP in the 0–10 cm layer. Soil CAT activity also decreased in 0–20 cm layer for HN and HNP in comparison with HP. The relative abundance of Actinobacteria increased by 38.1 and 45.0% in HC over that in CC and LC, respectively, in 0–10 cm soil; compared with LC, it increased by 35.8 and 21.7% in LN and LNP, respectively. The relative abundance of Proteobacteria was increased in LNP versus LC in 0–10 cm soil. Overall, fertilizer application coupled with a light grazing intensity promoted key soil properties and the relative abundance of a dominant bacterial phylum.